Assessment of the use of vanadium redox flow batteries for energy storage and fast charging of electric vehicles in gas stations. (15th November 2016) - Cunha, Álvaro; Brito, F.P.; Martins, Jorge; Rodrigues, Nuno; Monteiro, Vitor; Afonso, João L.; Ferreira, Paula
Abstract: A network of conveniently located fast charging stations is one of the possibilities to facilitate the adoption of Electric Vehicles (EVs). This paper assesses the use of fast charging stations for EVs in conjunction with VRFBs (Vanadium Redox Flow Batteries). These batteries are charged during low electricity demand periods and then supply electricity for the fast charging of EVs during day, thus implementing a power peak shaving process. Flow batteries have unique characteristics which make them especially attractive when compared with conventional batteries, such as their ability to decouple rated power from rated capacity, as well as their greater design flexibility and nearly unlimited life. Moreover, their liquid nature allows their installation inside deactivated underground gas tanks located at gas stations, enabling a smooth transition of gas stations' business model towards the emerging electric mobility paradigm. A project of a VRFB system to fast charge EVs taking advantage of existing gas stations infrastructures is presented. An energy and cost analysis of this concept is performed, which shows that, for the conditions tested, the project is technologically and economically viable, although being highly sensitive to the investment costs and to the electricity market conditions. Highlights: Assessment of Vanadium Redox Flow Battery use for EV fast charge in gas stations. This novel system proposal allows power peak shaving and use of deactivated gas tanks. Philosophy allows seamless business transition towards the Electric Mobility paradigm. Project is technologically and economically viable, although with long payback times. Future Cost cuts due to technology maturation will consolidate project attractiveness.